2018
DOI: 10.1590/1983-40632018v4851874
|View full text |Cite
|
Sign up to set email alerts
|

Macro and micronutrients uptake in biomass sorghum

Abstract: Biomass sorghum [Sorghum bicolor (L.) Moench] is a very promising renewable source to produce energy obtained by cogeneration and fermentation processes. However, some aspects of the fertilizer management for this crop should be better understood. This study aimed to determine the accumulation progress of dry matter and macro and micronutrients in phenological stages of the biomass sorghum (Palo Alto 2562) crop, as well as to establish the accumulation order. The experiment was performed in a randomized block … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 20 publications
0
12
0
2
Order By: Relevance
“…We observed that the highest estimated K accumulation in shoot biomass was 316.1 kg ha -1 , at the estimated dose of 134.8 kg ha -1 K, so the amount of K present in the soil was sufficient to nourish the plant. In this context, the high content of K in the soil may have covered the effect of K fertilization, even for biomass sorghum, which presents a very high capacity of K accumulation (Cavalcante et al, 2018). It is important to point out that the maximum accumulation of K in this study has not produced highest DM production, presenting that the biomass sorghum has a luxury characteristic for K consumption.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…We observed that the highest estimated K accumulation in shoot biomass was 316.1 kg ha -1 , at the estimated dose of 134.8 kg ha -1 K, so the amount of K present in the soil was sufficient to nourish the plant. In this context, the high content of K in the soil may have covered the effect of K fertilization, even for biomass sorghum, which presents a very high capacity of K accumulation (Cavalcante et al, 2018). It is important to point out that the maximum accumulation of K in this study has not produced highest DM production, presenting that the biomass sorghum has a luxury characteristic for K consumption.…”
Section: Discussionmentioning
confidence: 75%
“…In a 4year experiment in North Carolina, USA, variation in removal of K by variety Blade ES5200 from 187 to 205 kg ha -1 of K was reported (Heitman et al, 2017). In Goiás, Brazil, an absorption accumulation curve experiment with the hybrid Palo Alto 2562 found an accumulation of 447 kg K ha -1 for a DM production of 24.4 Mg ha -1 (Cavalcante et al, 2018). For the other nutrients, in the condition of highest DM productin (21,5 Mg ha -1 with 0 kg ha -1 K) the accumulation in the shoot followed the order of: K ~ Ca > N > Mg > P > S > Fe > Zn > Mn > B > Cu.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…And the sorghum stalks provide extra straw for fertilizing the next crop. Moreover, farmers obtain excellent profitability [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…And the sorghum stalks provide extra straw for fertilizing the next crop. Moreover, farmers obtain excellent profitability [32]. According to the planting instructions of NexSteppe, five steps were implemented during the growth of PALO ALTO Biomass Sorghum, which included seed dressing, sowing, fertilizing, weeding, and fertilizing for a second time, as shown in Additional file 1: Appendix D. During field experiments, crop growth status was monitored and reported weekly, as shown in appendix E. The harvest date was November 4, 2014, and yield per hectare was 63,000 kg/ha.…”
Section: Data Preparation Field Experiments On Sweet Sorghum Cultivatmentioning
confidence: 99%